Dexmedetomidine alleviates nerve injury induced by propofol in neonatal rats - ZHANG Fangling, ZHANG Yuanfang, ZHANG Li (Jichu yixue yu linchuang)
Objective To investigate the effect of dexmedetomidine (Dex) on propofol-induced nerve injury in neonatal rats. Methods The rats were divided into control group, intra-peritoneally injected propofol to construct nerve injury model group (50 mg/kg), Low, medium and high dose dexmedetomidine intervention model groups (Dex-L, Dex-M and Dex-H with femoral vein injection of 0.25, 0.5 and 1 μg/kg Dex, respectively), and Dex-H+anti-BDNF (10 0μg/kg) group, with 12 animals in each group. The neurological deficit score, number of platform jumping errors, and changes in brain index were detected in rats. HE staining microscopy was applied to measure pathology in the hippocampal CA1 region. ELISA was applied to detect level of interleukin-6 (IL-6), monocyte chemotactic protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α) in the hippocampal CA1 region. TUNEL staining microscopy was used to measure neuronal apoptosis in the hippocampal CA1 region. Western blot was applied to measure the cleaved caspase-3, proBDNF, mature brain-derived neurotrophic factor (mBDNF), phosphorylated tyrosine kinase B (p-TrkB), and phosphorylated phosphatidylinositol 3 kinase (p-PI3K) proteins in the hippocampal CA1 region. Results Compared with model group, the neuronal damage in rats was improved in Dex-L group, Dex-M group, and Dex-H group, the neurological deficit score, number of platform jumping errors, brain index, level of IL-6, MCP-1, TNF-α in hippocampal CA1 region, neuronal apoptosis rate, and level of cleaved caspase-3 and pro BDNF proteins all reduced, mBDNF, p-TrkB, and p-PI3K proteins in the hippocampal CA1 region raised(P＜0.05). Anti-BDNF inhibited the effect of 1 μg/kg Dex pretreatment on propofol induced nerve injury in neonatal rats. Conclusions Dex pretreatment inhibits neuro-inflammation and neuronal apoptosis, thereby reduces propofol induced nerve injury in neonatal rats. Its mechanism may be related to the activation of the mBDNF/TrkB/PI3K pathway.